An open source 3D printed autosampler for capillary electrophoresis - Itterheimová, Petra; Kubáň, Petr (Analytica chimica acta, 2023)
BACKGROUND: In-house built capillary electrophoresis (CE) systems represent a significant share of laboratory instrumentation. In most of these instruments, sample injection is effected manually with low to moderate precision and requires skilled operators. Although few automated samplers have been previously developed, typically only one sample at a time can be injected. If a series of samples is to be analyzed, manual intervention is required. In the present work, we developed and constructed a fully automated, open source, CE autosampler, able to handle up to 14 different samples that can be used as a modular component of any in-house built CE instrument. RESULTS: An inexpensive, 3D printed, open source, autosampler for CE was developed. The autosampler consists of two parts: an injection unit with carousel containing sample and electrolyte vials and a flushing unit, containing a miniature pressure/vacuum pump. The autosampler is operated by an Arduino Mega microcontroller and an Arduino code written in the laboratory. The injection sequence is entered through a keypad and LCD display by the user. The instrument can operate autonomously for extended periods of time. It was used for fully automated analysis and/or calibration of up to 14 samples with excellent injection repeatability reaching less than 2.7% RSD for peak areas. The sampler performance was tested with two independently built CE instruments, a CE system with contactless conductivity detection (C4D) and a CE system with laser induced fluorescence (LIF) detector. SIGNIFICANCE AND NOVELTY: A novel, 3D printed, Arduino-based autosampler for CE was developed. The autosampler allows autonomous hydrodynamic injection of up to 14 different samples with fully programmable injection sequence, including capillary flushing and high voltage and data acquisition control. It provides the missing instrumental sampling setup for laboratory made CE instruments. It can be simply constructed based on the open-source blueprints in any laboratory and be a useful and time-saving add-on to any modular CE instrument.
Keywords: Autosampler; Capillary electrophoresis; Open source hardware and software; Arduino